Antara Autentisitas dan Kepastian Hukum: Analisis Terhadap Akta Pernyataan Keputusan Rapat yang Tidak Dibacakan di Hadapan Notaris - Kusumawati, Raden Krishnaputri Devi; Martanti, Yurisa; Prasetyo, Dedy Ardian (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
The Deed of Statement of Meeting Resolution, as an authentic deed, must be read and signed before a notary in accordance with Article 16 paragraph (1) letter (m) of the Notary Office Law. In practice, however, this requirement is often neglected, leading to legal uncertainty. This study aims to analyze the legal consequences and legal certainty of deeds that are not read and signed before a notary. The research applies normative juridical methods with legislation, case, and conceptual approaches, supported by legal literature as primary and secondary sources. The analysis uses legal interpretation and construction techniques. The findings show that the absence of reading and signing before a notary nullifies the authenticity of the deed, resulting in new legal conditions, the alteration or termination of legal relationships, and potential sanctions. Legal certainty requires clear regulations, consistent application, approval by citizens, independent judiciary, and enforceable court decisions. The study recommends legal outreach by supervisory councils to notaries regarding due diligence principles and updated regulations, as well as public legal education on the validity of authentic deeds.